A CRITICAL REVIEW FROM THE PERSPECTIVE OF FUTURISTIC PEDAGOGY IN STUDENTS’ CHARACTER DEVELOPMENT - Sari, Atika; Rusmaini; Septika; Sri Nalyana; Merri Sri Hartati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In the modern era of rapid change, education is no longer solely focused on the transfer of knowledge but also on shaping students' character. In this context, character formation is not limited to moral or traditional ethical aspects but also includes the development of essential social and emotional skills for modern life. Character serves as a fundamental pillar that helps students face global challenges while adhering to moral values. Therefore, character development must encompass self-awareness, empathy, and the ability to make wise decisions amid a world full of choices and challenges. This article discusses how a critical review from the perspective of futuristic pedagogy can holistically support student character formation.